A systematic review and meta-analysis of patient data from the West Africa (2013–16) Ebola virus disease epidemic. (November 2019) - Rojek, A.M.; Salam, A.; Ragotte, R.J.; Liddiard, E.; Elhussain, A.; Carlqvist, A.; Butler, M.; Kayem, N.; Castle, L.; Odondi, L.'O.; Stepniewska, K.; Horby, P.W.
Abstract: Background: Over 28 000 individuals were infected with Ebola virus during the West Africa (2013–2016) epidemic, yet there has been criticism of the lack of robust clinical descriptions of Ebola virus disease (EVD) illness from that outbreak. Objectives: To perform a meta-analysis of published data from the epidemic to describe the clinical presentation, evolution of disease, and predictors of mortality in individuals with EVD. To assess the quality and utility of published data for clinical and public health decision-making. Data sources: Primary articles available in PubMed and published between January 2014 and May 2017. Eligibility: Studies that sequentially enrolled individuals hospitalized for EVD and that reported acute clinical outcomes. Methods: We performed meta-analyses using random-effect models and assessed heterogeneity using the I 2 method. We assessed data representativeness by comparing meta-analysis estimates with WHO aggregate data. We examined data utility by examining the availability and compatibility of data sets. Results: In all, 3653 articles were screened and 34 articles were included, representing 16 independent cohorts of patients (18 overlapping cohorts) and at least 6168 individuals. The pooled estimate for case fatality rate was 51% (95% CI 46%–56%). However, pooling of estimates for clinical presentation, progression, and predictors of mortality in individuals with EVD were hampered by significant heterogeneity, and inadequate data on clinical progression. Our assessment of data quality found that heterogeneity was largely unexplained, and data availability and compatibility were poor. Conclusions: We have quantified a missed opportunity to generate reliable estimates of the clinical manifestations of EVD during the West Africa epidemic. Clinical data standards and data capture platforms are urgently needed.